The Influence of Amiodarone Complexation with 2-Hydroxypropyl-\(β\)-Cyclodextrin in Oral Matrix Tablets Delivery: In vitro and In vivo Evaluation - Creteanu, Andreea; Pamfil, Daniela; Vasile, Cornelia; Ghilan, Alina; Tantaru, Gladiola (Progress in Chemical Science Research Vol. 9, 2023)
The aims of this study were to improve both the solubility of the amiodarone hydrochloride (AMD) and its controlled release from the inclusion complexes with 2-hydroxypropyl-\(β\)-cyclodextrin (HP-\(β\)-CD).The complexation with cyclodextrins (CDs) is a method to optimize the therapeutic performance of the insoluble drugs, including AMD. The inclusion complexes were prepared by co-precipitation and freeze-drying. The solubility enhancement of AMD/HP-\(β\)-CD inclusion complexes increase by 4–22 times was evaluated by the phase solubility method. The inclusion complexes were studied both in solution and in solid state by spectroscopic methods, dynamic light scattering (DLS), zeta-potential (ZP) analysis, scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). The obtained inclusion complexes (AMD/HP-\(β\)-CD) showed an increase in solubility by more than 200%. Two kinds of formulations have been tested namely of AMD/HP-\(β\)-CD inclusion complexes both as powdered form and as matrix tablets containing Kollidon®SR (KOL), Chitosan (CHT) and one containing only pure AMD as a control sample. The kinetics of AMD release form the two kinds of formulations was evaluated by in vitro and in vivo studies. The active substance release was followed by in vitro release testing and the results were analyzed by fitting into four representative mathematical models for the modified release oral formulations. The release of the active substance from the matrix modified tablets is dependent on its solubility degree in the dissolution medium as well as on the composition of the matrix forming polymers. It was found that both formulations showed superior pharmacokinetic performance by improving both loading and release properties in respect with those of the pure low soluble AMD drug. In vitro kinetic study reveals a complex mechanism of release which occurred in three steps, the first one is attributed to a burst effect and the other two to different bondings existing in inclusion complexes. Two factors have been calculated to assess the release profile of amiodarone: f1 - the similarity factor and f2 - the difference factor. Akaike index and the correlation coefficient were the criteria used for selecting the model that most faithfully depicted the release profile of each studied formulation. In vivo tests on complexed aminodarone loaded in matrix tablets containing KOL and CHT revealed a multiple (at least two) peaks release diagram because of both structure of the inclusion complexes and also of different sites of absorption in biological media (digestive tract).